Dimensions of emotion dysregulation associated with problem video gaming. (2nd January 2020) - Hollett, Kayla B.; Harris, Nick
Abstract: Background and Purpose: Emotion dysregulation is characterised by difficulties monitoring, understanding, and accepting uncomfortable emotions and may lead some individuals to attempt to attenuate or escape emotional experiences by engaging in distracting activities, such as video gaming. Preliminary findings suggest that some dimensions of emotion dysregulation may be related to problem video gaming, but these findings are not generalisable to the general English-speaking population. The purpose of the current study was to determine whether dimensions of emotion regulation were associated with problem video gaming in a sample of self-reported video gamers from the general English-speaking adult population. Method: Self-identified adult video game players ( N = 928) completed an online survey including the Problem Video Game Playing Scale (PVP) and the Difficulties in Emotion Regulation Scale (DERS). Results: A sequential regression analysis revealed age and gender as statistically significantly predictors of problem gaming in the full sample, as well as two dimensions of emotion dysregulation: (1) difficulties with impulse control; and (2) perceived limited access to emotion regulation strategies. A second sequential regression analysis was conducted to explore if gender moderated the relationship between any DERS subscales and problem gaming, and no significant moderations were found. Conclusions: This study represents the first examination of emotion dysregulation and problem gaming in English-speaking adults and expands upon existing evidence supporting associations between specific dimensions of emotion dysregulation and problem video gaming.